(untitled) (Fiep Bulletin - online, 2012)
This study analyzes the contributions of physical education in kindergarten. At first discuss some of the history of early childhood education, followed by their educational goals at this level in order to see how has been given the job of teachers serving children 0-5 years. For this, we conducted an interview with six teachers from public municipal schools of the city of Astolfo Dutra / MG. The results showed that their understandings of Physical Education have reduced feeling well and that does not include its specificity. It also revealed that their representations about the work of physical education to early childhood education are positive visions and believe in its importance to the development of the child.